Anatomy & physiology made incredibly easy! - Scott, William N. (Philadelphia, Pennsylvania : Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
This title provides a thorough grounding for the essentials of biomedical science prescribed by the NMC and Universities. The content of this edition has been fully revised so that it covers all relevant areas and is placed firmly in the UK context for education and practice.
Includes bibliographical references (p. 357) and index
Keywords: Human anatomy -- Outlines, syllabi, etc; Human physiology -- Outlines, syllabi, etc